EXPLORING EFL STUDENTS’ PERCEPTION ON CLOUDX ONLINE LEARNING MEDIA OF ELEVENTH GRADE AT SMK NEGERI 1 TANJUNG SELOR - Idayanti, Nurul; Vega, Nofvia De; Ajisoko, Pangkuh (Universitas Borneo Tarakan, 2021)
This study aims to describe the perception of EFL students towards the onlinelearning media CloudX class XI at SMK Negeri 1 Tanjung Selor. This study uses aquantitative descriptive approach. Samples were taken as many as 70 respondentsfrom class XI SMK Negeri 1 Tanjung Selor. Data collection techniques are usingquestionnaires and interview guidelines. The results of the questionnaire wereanalyzed using descriptive statistical analysis and interview results as supportinginformation. The results of this study indicate that EFL students provide perceptionsof CloudX online learning media from the positive and negative sides. On thepositive side, students are helped to take distance learning at home through virtualmeetings using the CloudX application. In addition, there are several features suchas audio, video, chat rooms, and share screens to support students and teachers indiscussing and communicating in the online learning process. Therefore, studentscan easily understand the learning topic because the teacher can share and explainthe material at the same time. Furthermore, the CloudX app also provides a positiveexperience with students. For example, students can know how to use technology (egCloudX). However, EFL students also gave negative perceptions of online learningthrough CloudX. Based on the results of the study, sometimes online learningthrough CloudX is not effective because there are several obstacles such as studentsnot having a good internet connection and not all students having adequate facilities(such as smartphones or laptops) as supporting devices to attend virtual meetingsthrough CloudX. On the other hand, most students prefer to share and discuss ideaswith peers and colleagues, responding to online discussions in traditional face-tofaceclassesasinnormalsituationsbeforedistanceeducationwasimplemented.